Primary hepatic tuberculosis masquerading as cholangiocarcinoma: A clinical nugget - Shera, Irfan Ali; Shawl, Muzafar Rashid; Rajan, Prem; Soni, Ram Chandra (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Shera IA, Shawl MR, Rajan P, Soni RC. Primary hepatic tuberculosis masquerading as cholangiocarcinoma: A clinical nugget. Turk J Gastroenterol 2019; 30(8): 764-6.